PERAN MANAJEMEN PEMBELAJARAN DALAM MENINGKATKAN PRESTASI BELAJAR SISWA MELALUI PENGGUNAAN ALAT PERAGA SEDERHANA - Titik Tri Prastawati; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
One of the quality of education can be seen in the achievement of student learning achievement. If the score is above the average minimum completeness limit, it can be interpreted that student learning achievement is said to be high. This requires an effort from Learning Management that involves all components in the school, one of which is the teacher. The teacher is one of the main factors for the success of teaching and learning. Teachers are required to be active, creative and innovative in order to be able to carry out learning tasks. The implementation of learning management is a collaboration between school leaders and teachers to transfer knowledge through various concepts/methods. Through collaboration and communication, it will create a synergistic harmony in order to achieve an increase in student learning achievement. Improving student achievement must continue to be done to answer the challenges of the times and produce quality graduates. This is a shared and inseparable task so it is necessary to always work together to find the right formula in delivering subject matter that is familiar to students and raises students' creativity and mindset.